Perspectives for immunotherapy of EBV‐associated GLELC: A relatively “hot” tumor microenvironment - Yanna Lei; Peng Cao; Xiufeng Zheng; Jing Wei; Mo Cheng; Ming Liu (Cancer Medicine, 2023)
Abstract Background Epstein–Barr virus (EBV)‐associated gastric lymphoepithelioma‐like carcinoma (EBVaGLELC) represents a small number of gastric cancer (GC), and research on tumor microenvironment (TME) and treatment strategy are still lacking. Aims Here, we aim to elucidate the immune features of this rare disease and further help to develop more effective treatment options. Materials & Methods A retrospective analysis was conducted between 2019 to 2022 in West China Hospital to reveal the immunological characteristics of EBV‐positive GLELC. The difference of immune cell subset and tumor vascular structure between gastric denocarcinoma (GAC) and EBVaGLELC will be pointed out. Discussion 13 patients with GELEC and 8 patients with GAC were retrospectively studied. The heterogeneity of the immune cell profile was then confirmed through multiplexed immunofluorescence staining (mIF), which revealed a higher proportion of CD3+ T cells, CD8+ T cells, and Treg cells in the EBV‐associated GLELC group. Such a distinct TME may provide therapeutic advantages, and patients with this rare subtype of GC could be good candidates for immune checkpoint inhibitors (ICIs). Angiogenesis in EBV‐positive GLELC may be less intense than that in gastric adenocarcinoma (GAC), a feature that might decrease their susceptibility to antiangiogenic therapy. Furthermore, we reported a 52‐year‐old male with advanced EBV‐positive GLELC who showed a favorable response to the combined therapy with . A repeat evaluation showed sustained partial response (PR), and the progression‐free survival (PFS) was more than 34 months until now. Conclusion Compared with GAC, EBVaGLELC revealed higher T cell infiltration and less intense of angiogenesis. It displays relatively “hot” TME that may provide the rationality to treat with immunotherapy in EBV‐related GLELC.